Conflicts in the Boardroom Survey : Results and Analysis - International Finance Corporation; Centre for Effective Dispute Resolution (International Finance Corporation, Washington, DC, 2017)
In the boardroom, disagreements are often unavoidable - especially when the board is composed of independent minded, skilled, and outspoken directors. A board that never argues or disagrees is most likely to be an inactive, passive, or inattentive board - in other words, an ineffective board that is neither fulfilling its oversight function nor carrying out its duty of care. If boardroom disagreements and or shareholder conflicts are not dealt with properly, they can devolve into acrimonious disputes that undermine a company’s operation and performance. Left unchecked and unattended, these disputes escalate quickly into public matters that can have severe, long-term consequences for the company and its key stakeholders. These disputes can lead to poor performance, scare investors, produce waste, divert resources, cause share values to decline, and, in some cases, paralyze a company. In 2012, the center for effective dispute resolution (CEDR) and the corporate governance group of the International Finance Corporation (IFC) undertook a joint project to explore the causes, nature, and methods of resolving corporate governance disputes. As part of this ongoing project, CEDR and IFC carried out a global survey. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.